Epidemiology and molecular characterization of invasive disease in children twenty years after the implementation of Haemophilus influenzae serotype b vaccine in Portuguese Immunization Programme - Bajanca-Lavado, Maria Paula (2022)
Background: Haemophilus influenzae is an important human pathogen responsible for severe childhood invasive disease, despite the implementation of the vaccine against serotype b isolates (Hib), in our National Immunization Programme (NIP), in June 2000. The use of the vaccine lead to a reduction in Hib invasive disease, together with the emergence of non-encapsulated (NTHi), and capsulated non-b-type isolates. This study aims to characterize H. influenzae invasive disease in children, twenty years after the introduction of the Hib vaccine in NIP. Methods Hundred-twenty invasive H. influenzae isolates collected from children in 33 Hospitals, between January 2010 and December 2020, were characterized at the National Reference Laboratory for Haemophilus influenzae. Antibiotic susceptibility was assessed by a microdilution assay. Capsular status was identified by PCR as previously described. MLST was performed as described in the literature. Sequences were analysed and submitted to the MLST website (https://pubmlst.org/hinfluenzae/) for assignment of the sequence type (ST). goeBURST analysis was performed using the PHYLOViZ platform. Results Childhood invasive disease was mainly due to NTHi (55.8%; 67/120), although Hib still in circulation (29.2%; 35/120). Twenty-two cases of vaccine failures were responsible for 62.9% of Hib disease, with 59% of cases occurring in last four years. Non-b capsular types isolates were distributed as follow: 9.2% serotype a (11/120), 1.6% serotype e (2/120) and 4.2% serotype f (5/120). Most isolates were susceptible to all antibiotics studied, with 8.3% (10/120) being ampicillin resistant by β-lactamase producing. MLST revealed, as expected, high genetic variability (77.1%), with 37 different STs among 48 NTHi isolates. In opposition, encapsulated isolates were clonal with Hia assigned to CC23 (ST23-n=6; ST1511-n=1), Hib to CC6 (ST6-n=27, ST190, ST1149 and ST1231 with one isolate each), Hie to CC18 (ST18-n=2) and Hif to CC124 (ST124-n=2, ST1188-n=1). Conclusions Our data suggests that after vaccine implementation, invasive disease among Portuguese children is mainly due to highly genetically diverse, susceptible NTHi isolates. Nevertheless, we are concerned about Hib disease (~30%) despite the higher vaccine coverage observed in our country. Ongoing surveillance should be continued, in order to monitor the burden of the disease, especially Hib, and develop additional public health prevention strategies.